Detection of Vgsc-L1014F Allele Knockdown-resistance Mutation in Male Culex quinquefasciatus - Mahfudhah, Dzikra Nasyaya; Rahmafitria, Fistara Lesti; Hari Sucipto, Teguh; Fauziyah, Shifa; Anggarani, Mirwa Adiprahara; Herdyastuti, Nuniek; Naw, Sin War; Witaningrum, Adiana Mutamsari (HAYATI Journal of Biosciences, 2025)
The distribution of Culex quinquefasciatus as a vector for several tropical diseases in Indonesia could affect the transmission of various pathogens, including filariasis, West Nile, encephalitis, and Rift Valley fever. The use of insecticides to control mosquito populations is carried out massively. However, this effort is threatened by an increase in mosquito resistance to insecticides, in this case, pyrethroids that target Voltage-gated sodium channel (VGSC) as a complex protein in mosquito nerve cells that plays a role in the movement of sodium ions, where these compounds can have a knockdown effect and lead to death. The existence of a single nucleotide mutation in this specific codon results in knockdown resistance (kdr) in mosquitoes. This study aims to determine whether there is a kdr mutation in the Vgsc-L1014F target using the latest molecular method ETAS-PCR to type tri-allelic variation at Vgsc-1014 in Cx. quinquefasciatus samples collected in three areas in the cities of Surabaya and Sidoarjo, namely Wonocolo, Sukodono, and Wonoayu. The result showed ten male pool samples (C1-C10) of Cx. quinquefasciatus did not carry mutations or present as homozygous wild type (TTT/TTT), with a DNA band size of 181 bp. Hence, this preliminary study could be extended for further research to build vector control monitoring programs.